2020
DOI: 10.3386/w27506
|View full text |Cite
|
Sign up to set email alerts
|

International Migration Responses to Modern Europe’s Most Destructive Earthquake: Messina and Reggio Calabria, 1908

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…As we noted previously though, the (de)stabilizing nature of migration could critically depend on the type of resident migration. Consistent with evidence in modern data on sorting near high-risk flood zones (Bakkensen and Ma 2020), and migration following natural disasters (Boustan et al 2012;Mahajan & Yang 2020;Spitzer et al 2020), Hornbeck (2020) shows that Dust Bowl migrants were "negatively selected" via lower education and likely lower income. 7 An important difference in our case is that migration is responding to future expectations, which means that it affects future responses to climate change.…”
supporting
confidence: 64%
“…As we noted previously though, the (de)stabilizing nature of migration could critically depend on the type of resident migration. Consistent with evidence in modern data on sorting near high-risk flood zones (Bakkensen and Ma 2020), and migration following natural disasters (Boustan et al 2012;Mahajan & Yang 2020;Spitzer et al 2020), Hornbeck (2020) shows that Dust Bowl migrants were "negatively selected" via lower education and likely lower income. 7 An important difference in our case is that migration is responding to future expectations, which means that it affects future responses to climate change.…”
supporting
confidence: 64%
“…This might be motivated by the fact that the European continent is mostly seen as a destination for migrants than an origin. It should not surprise that the two articles covering European countries, namely Italy (Spitzer et al, 2020) and the Netherlands (Jennings and Gray, 2015) analyze historical data of mobility at the beginning of the XX century (respectively earthquake in Sicily and Calabria and climate variability associated with riverine flooding in the Netherlands). Nevertheless, figures show that Europe is not unrelated to the occurrence and frequency of hazards as well as to sizable internal mobility that should receive some attention.…”
Section: Overview Of Major Resultsmentioning
confidence: 99%
“…When it happened, many people chose to migrate abroad from southern Italy as the international borders were open, facilitating the migration choice as a response. (Spitzer et al 2020) showed the effects of this earthquake on international migration from Italy to other EU countries and the US and found that, on average, this disaster positively affected migration. There was heterogeneity in the people's responses, with a more positive relation with agricultural laborers comprising the other share of the labor force.…”
Section: Fast-onset Environmental Eventsmentioning
confidence: 99%
“…For example, the Messina-Reggio Calabria earthquake in Italy destroyed the state's capital and massively affected people's living standards and wealth. Hence, their sources of income and financial safety were highly diminished, so staying in their home state was no longer an option (Spitzer et al 2020). There is a debate on the effect of environmental shocks.…”
Section: Introductionmentioning
confidence: 99%